Numerical and experimental investigation of the steering performance of a ringsail parachute - HUANG Yunyao; WU Shiqing; WANG Yongbin; ZHANG Yang (Xibei Gongye Daxue Xuebao)
In order to investigate the steering performance of the ringsail parachute, the effect of two different steering approaches on the aerodynamic and gliding characteristics of a ringsail parachute is analyzed by using the numerical simulation and wind tunnel test. The first steering approach is to make ringsail parachute drift off course by changing the length of the suspension lines, while the second one is to make ringsail parachute close up by changing the length of the reefing control lines. Numerical simulation is performed using the arbitrary Lagrangian-Eulerian fluid-structure interaction method, and the corresponding wind tunnel test is conducted to compare with the results of numerical simulation. The results show that the first steering approach can effectively change the drag coefficient of the ringsail parachute, i.e., the drag coefficient is greatly reduced as the length of the suspension lines is shortened, and in the meanwhile, compared with the non-steering ringsail parachute, the improvement of the gliding ratio can be up to 80%, which demonstrates the benefits for the gliding ability; While the second steering approach has an significant impact on the drag characteristics of the ringsail parachute, i.e., as the length of reefing control lines is shortened, the reefing effect is enhanced and the drag characteristics is reduced, whereas compared with the non-steering ringsail parachute, the improvement of the gliding ratio only reaches up to 10%, which demonstrates that the reefing control has little effect on the gliding performance. Comparison between the results obtained by the wind tunnel test and numerical simulation shows that the trend of drag coefficient and drag characteristic curves are basically consistent, and the relative error between them is within 20%, indicating the reliability of the numerical method.